Cyrus Młodszy, Tissafernes i miasta jońskie, 403–402 r. przed Chr. - Podrazik, Michał (Instytut Historyczny Uniwersytetu Wrocławskiego, 2019)
The events of the years 403–402 BC of Achaemenid Asia Minor are relatively poor illuminated by our sources. This article focuses onthe events taking place mainly in the western part of the peninsula, analyzing the ongoing relations between Cyrus the Younger, Tissaphernes and the Ionian cities.